Effect of GPIIb/IIIa inhibition with eptifibatide or tirofiban on the expression of cellular adhesion molecules on monocytes - Swoboda, Stefanie; Walter, Thomas; Lang, Siegfried; Wendel, Hans-Peter; Beyer, Martin E.; Griesel, Eva; Hoffmeister, Hans-Martin; Grüttner, Joachim (In vivo, 2014)
Aim: The aim of the present study was to investigate the effect of GPIIb/IIIa inhibition with eptifibatide and tirofiban on the expression of cellular adhesion molecules on monocytes at different temperatures. Materials and Methods: Circulation of blood from six volunteers was performed in an extracorporal circulation model at 36°C and 18°C for 30 min. The blood of each donor was prepared either with addition of eptifibatide or tirofiban, or was left untreated as control. CD54 and CD162 on monocytes was measured using flow cytometry. Results: Expression of CD11b was lower at 18°C compared to 36°C by 51% in the eptifibatide group (p=0.0043), by 29% in the tirofiban group (p=0.095) and by 34% in the control group (p=0.038). Expression of CD54 was not significantly different at 18°C compared to 36°C, neither with eptifibatide (p=0.29) nor tirofiban (p=0.48) nor in the control group (p=0.26). Expression of CD162 was lower at 18°C compared to 36°C by 40% using eptifibatide (p=0.0010), by 94% using tirofiban (p=0.0095) and by 34% in the control group (p=0.019). At 36°C and 18°C, no significant differences were found regarding the expression of CD11b, CD54 and CD162 between the eptifibatide-treated group, the tirofiban-treated group and the control group. Conclusion: GPIIb/IIIa inhibition with eptifibatide or tirofiban seems to have no effect on the expression of CD11b, CD54 and CD162 on monocytes during normothermia or hypothermia. Our results show that the beneficial effect induced by hypothermia on the extracorporal circulation-associated alteration of leukocyte function, with decreased expression of CD11b and CD162, seems not to be affected by additional treatment with eptifibatide or tirofiban.